Efeitos da suplementação de proteína no músculo sóleo, de ratos obesos não exercitados, durante restrição calórica - Pasqual, Julia (Universidade Federal de São Carlos, 2025)
Obesity is one of the main triggering factors for various chronic diseases, leading to significant changes in tissues such as skeletal muscle. The great increase in pro- and anti-inflammatory myokines during this process may compromise the trophic and functional aspects of the muscle. Nutritional therapies, such as caloric restriction (CR), have been studied and shown to be effective against obesity. However, depending on the duration and magnitude, CR may lead not only to fat loss, but also to the loss of lean mass (skeletal muscle), further impairing the morphology and function of the tissue. To minimize this loss, strategies such as protein supplementation have proven effective in trained muscles, but little is known about their effects on skeletal muscle under weight-loss-specific conditions. Therefore, this study aims to analyze the effects of animal protein supplementation on the tropism and fiber types of the soleus muscle in obese rats under caloric restriction. Methods: Forty-two male Wistar rats (Rattus norvegicus) were used and divided into seven groups (n= 6): 8 Week Control (GC8), 16 Week Control (GC16), Obese (GO), ad libitum (Gal), 20% Caloric Restriction (GDC20), 60% Caloric Restriction (GDC60), and Caloric Restriction with Protein Supplementation (GWP). After the procedures, the animals were euthanized under anesthesia and the soleus muscle was excised for histological and morphometric analysis. Based on the analysis of the results obtained, it can be concluded that protein supplementation in the diet of animals under 60% calorie restriction acted as a protective factor in skeletal muscle tissue, preserving the diameter of the soleus muscle fibers.
Effects of protein supplementation on the soleus muscle of non exercise obese rats, during caloric restriction
Keywords: Músculo esquelético; Obesidade; Proteína; Restrição calórica; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS